Jenis-Jenis Serangga Pengunjung Bunga Pacar Air (Impatiens balsamina Linn. :Balsaminaceae) - Nadra Khairiah; - Dahelmi; - Syamsuardi (Universitas Andalas, 2012)
A study of visitor insects to the flower of Impatiens balsamina Linn. has been conducted in two locations, i.e. Ulu Gadut, Bandar Buat, Lubuk Kilangan Subdistrict, Padang City and Koto Tinggi, Surian, Pantai Cermin Subdistrict, Solok Regency in February 2012. The purpose of the study was to determine the species of visitor insects of the flowers of Impatiens balsamina. Direct collection method by using insect net was used in this study. Insects were identified at Laboratory of Animal Taxonomy, Biology Department, Faculty of Mathematics and Natural Sciences, Andalas University, Padang. The results showed that 16 species of insects that belong to 16 genera, 9 families and 3 orders were recorded. The visitor insects were dominated by Hymenoptera order (68.75%) followed by Lepidoptera (18.75%) and Diptera (12.50%).Keywords: Impatiens balsamina, insects, visitors, flower, species